Resolving identity-based violence: Lessons for restorative justice in the hate crime context - Malini Laxminarayan (Droit et Cultures)
Restorative justice has expanded its application of different types of crimes; including, but not limited to, violations such as sexual violence, domestic violence and more recently violent extremism, to name a few. The severity of these crimes, combined with the fact that restorative justice has been applied successfully to these complex offences, suggests that hate crimes should not be ruled out as potential cases. What is missing, however, is a better understanding of what makes these crimes unique, and how restorative justice can or cannot play a role in responding to the harm caused because of hate and identity-based attacks. By looking at evidence and theory from other fields, namely peacebuilding in this analysis— in addition to understanding hate and bias more generally, this article attempts to develop a theoretical framework for better understanding restorative justice in cases of anti-LGBT hate crime and briefly considers what such a framework may entail for practice.¨My starting point is that people are good, most do not mean to cause harm. There of course is a hardcore group where it truly is hate on an ideological level, and people [rightly] ask, can you change them? But there is a bigger group that needs that [RJ] meeting, to get to know the other person, and to change as a result of it. ¨ Mediator, Belgium, LetsGoByTalking project